Small grid-connected PV-system with lossless passive soft-switching technique - D. Amorndechaphon (2018)
In order to increase the system efficiency of small grid-connected PV-systems without resulting to complex control, a high-efficiency PV power inverter with simple control methodology is required. To satisfy this requirement, an improved single-phase inverter using soft-switching technique is proposed. The power circuit is composed of a lossless passive snubber boost converter and a LLCC resonant inverter. The operating principles of the proposed small grid-connected PV-system will be thoroughly discussed. The effectiveness and result of the proposed grid-connected inverter for small PV system is verified by simulation. © 2009 SICE.